2005
DOI: 10.1377/hlthaff.w5.509
|View full text |Cite
|
Sign up to set email alerts
|

Taking The Pulse Of Health Care Systems: Experiences Of Patients With Health Problems In Six Countries

Abstract: This paper reports on a 2005 survey of sicker adults in Australia, Canada, Germany, New Zealand, the United Kingdom, and the United States. Sizable shares of patients in all six countries report safety risks, poor care coordination, and deficiencies in care for chronic conditions. Majorities in all countries report that mistakes occurred outside the hospital. The United States often stands out for inefficient care and errors and is an outlier on access/cost barriers. Yet no country consistently leads or lags a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(217 citation statements)
references
References 11 publications
5
204
0
8
Order By: Relevance
“…Surveys of Australian medicine users consistently find substantial numbers of Australians reporting difficulties with meeting the cost of their prescriptions. [61][62][63][64] Difficulty with cost is reported as the reason for not obtaining a prescription medicine by around 20% of respondents. 61,63,65 A recent analysis of national dispensing data has confirmed the negative impact of increasing copayments on pharmaceutical affordability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of Australian medicine users consistently find substantial numbers of Australians reporting difficulties with meeting the cost of their prescriptions. [61][62][63][64] Difficulty with cost is reported as the reason for not obtaining a prescription medicine by around 20% of respondents. 61,63,65 A recent analysis of national dispensing data has confirmed the negative impact of increasing copayments on pharmaceutical affordability.…”
Section: Resultsmentioning
confidence: 99%
“…[61][62][63][64] Difficulty with cost is reported as the reason for not obtaining a prescription medicine by around 20% of respondents. 61,63,65 A recent analysis of national dispensing data has confirmed the negative impact of increasing copayments on pharmaceutical affordability. 64 Decreases in utilisation following increase in copayment and safety net level were observed for essential as well as discretionary medicines and the greatest impact was among social security beneficiaries.…”
Section: Resultsmentioning
confidence: 99%
“…This compares with consumer surveys in which half of patients reported being able to get same day appointments in Australia ahead of the UK, Canada and US, but behind New Zealand and Germany. 19 A higher proportion of Australian GPs reported arrangements for afterhours access than those in the US and Canada, but lower than those in the UK and New Zealand. The pattern of associations of the two measures of access with practice and practitioner characteristics was quite different.…”
Section: Discussionmentioning
confidence: 96%
“…In the 1990s, people in the US reported much lower satisfaction with their health care systems than did Canadians, Western Europeans and the Japanese (Isaacson, 1993). A 2005 survey of six wealthy nations found that "the US often stands out for inefficient care and errors" (Schoen et al, 2005). A massive survey of 82,583 Medicare patients in 182 health plans found that non-profit health plans scored higher than for-profit on measures of overall quality, access to care and customer service (Landon et al, 2001).…”
Section: Friedman's Microeconomics: What's Wrongmentioning
confidence: 99%